An Inside Look at Teacher Stress: Is Teaching (Un)stressful? (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The article concerns stress as a factor influencing lives of many teachers. Teaching can be a stressful profession and stress may affect career motivation and diminish effectiveness and job satisfaction of many loyal and gifted teachers. They are facing many different sources of stress. It comes of no surprise that stress levels among teachers are still increasing. There are presented particular personality traits that are somehow related to different reactions on stress and the way people handle it. The study was conducted to illustrate the problems that teachers struggle with. The results of the questionnaire are supposed to show the advantages, drawbacks and consequences of stress occurring in the workplace.